FINANCIAL DISTRESS DETERMINANTS IN INFRASTRUCTURE FIRMS: THE ROLES OF AUDIT COMMITTEES, FINANCIAL INDICATORS, AND OWNERSHIP STRUCTURE WITH PROFITABILITY AND FIRM VALUE EFFECTS - Mohamad Zulman Hakim; Fakhra Aura Febriawanto; Anggun Ardianih; Mulyanti; Alya Fakhirah Mashuri (ZILLZELL MEDIA PRIMA, 2026)
This study aims to examine the influence of audit committees, sales growth, liquidity, leverage, and institutional ownership on financial distress, with profitability as a moderating variable and company value as a mediating variable. The research object includes infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. From a total population of 70 companies during the five-year observation period, 12 companies were selected as samples using purposive sampling. The results show that liquidity has a significant effect on financial distress. Meanwhile, the audit committee, leverage, institutional ownership, and sales growth do not have a significant effect on financial distress. Furthermore, profitability moderates the relationship between leverage and financial distress, but does not moderate the effect of the audit committee, liquidity, institutional ownership, and sales growth on financial distress. Moreover, company value acts as a mediating variable in the relationship between sales growth, liquidity, and leverage on financial distress, but does not mediate the relationship between the audit committee and institutional ownership on financial distress.